2012
DOI: 10.1002/bio.2395
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted aqueous synthesis of new quaternary‐alloyed CdSeTeS quantum dots; and their bioapplications in targeted imaging of cancer cells

Abstract: In this study, we report for the first time a one-pot approach for the synthesis of new CdSeTeS quaternary-alloyed quantum dots (QDs) in aqueous phase by microwave irradiation. CdCl2 was used as a Cd precursor during synthesis, NaHTe and NaHSe were used as Te and Se precursors and mercaptopropionic acid (MPA) was used as a stabilizer and source of sulfur. A series of quaternary-alloyed QDs of different sizes were prepared. CdSeTeS QDs exhibited a wide emission range from 549 to 709 nm and high quantum yield (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…CdTeSe cores were prepared following amodified method described in [9][10][11][12][13][14]. Core-shell alloy quantum dots were prepared according to a modified SILAR protocol that has been previously published [13].…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…CdTeSe cores were prepared following amodified method described in [9][10][11][12][13][14]. Core-shell alloy quantum dots were prepared according to a modified SILAR protocol that has been previously published [13].…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…The strong fluorescent stability of QDs also shows superiority in research on living animal. In recent years, Ren et al have reported CdSeTeS QDs modified with alpha-thioomega-carboxy poly(ethylene glycol) (HS-PEG-COOH), and the modified QDs were linked to anti-epidermal growth factor receptor (EGFR) antibodies [62]. QDs with the EGFR antibodies as labeling probes were successfully applied to targeted imaging for EGFR on the surface of SiHa cervical cancer cells through conjugation of QDs with the anti-EGFR antibodies.…”
Section: The Applications Of Quantum Dots In Tumor Diagnosticmentioning
confidence: 99%
“…The unprecedented research boom that has occurred over the past two decades with respect to the chemistry of semiconductor nanocrystal quantum dots (QDs) stems from their intriguing electronic and optical properties such as their high surface-tovolume-ratio, size-tunable photoluminescence (PL) spectra, narrow emission and broad absorption spectra, bright fluorescence and high resistance to photo-initiated degradation and CdSeTeS [24]. To the best of our knowledge, the synthesis of alloyed quaternary CdSeTeS core QDs, which is of interest in this work, have only been reported once in literature and they were synthesized via a microwave assisted aqueous method [24].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the synthesis of alloyed quaternary CdSeTeS core QDs, which is of interest in this work, have only been reported once in literature and they were synthesized via a microwave assisted aqueous method [24].…”
Section: Introductionmentioning
confidence: 99%